2012
DOI: 10.1371/journal.pone.0049735
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Growth of Congenital Solitary Kidneys in Pigs Reflects Increased Nephron Numbers Rather Than Hypertrophy

Abstract: BackgroundPatients with unilateral MultiCystic Kidney Dysplasia (MCKD) or unilateral renal agenesis (URA) have a congenital solitary functioning kidney (CSFK) that is compensatory enlarged. The question whether this enlargement is due to increased nephron numbers and/or to nephron hypertrophy is unresolved. This question is of utmost clinical importance, since hypertrophy is associated with a risk of developing hypertension and proteinuria later in life with consequent development of CKD and cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
2
27
1
Order By: Relevance
“…Animal studies confirmed that a compensatory increase in nephron number is present in congenital solitary functioning kidney (27,28). Nevertheless, the total nephron number identified is still lower than in two kidney controls (Table 2).…”
Section: Consequences Hyperfiltration Hypothesismentioning
confidence: 67%
“…Animal studies confirmed that a compensatory increase in nephron number is present in congenital solitary functioning kidney (27,28). Nevertheless, the total nephron number identified is still lower than in two kidney controls (Table 2).…”
Section: Consequences Hyperfiltration Hypothesismentioning
confidence: 67%
“…Van Vuuren used pig kidneys as a model for human kidneys for accurate determination of nephron size and number in a comparative analysis in slaughterhouse pigs with one or two kidneys. The mean total weight, cortex volume and mean number of glomeruli were 84%, 83% and 50% higher in the compensatory CSFKs than in the control kidneys respectively.…”
Section: Discussionmentioning
confidence: 97%
“…They observed a 45% increase in the number of nephrons in the kidneys from the unilaterally nephrectomized. In their study, and in contrast to the results of Van Vuuren et al , the mean glomerular volume in the unilaterally nephrectomized sheep was 26% lower than in controls and total glomerular volume per individual kidney was comparable in both groups. These findings may suggest differences in prenatal and postnatal compensatory mechanisms – increase in nephron number during fetal development and hypertrophic glomerular growth after birth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is a plausible explanation as reduced nephron endowment has long been postulated to correlate with risk for hypertension as well as renal disease. 33 In contrast to the HSRA model, many studies using other models of congenital solitary kidney (rat 34 or pig 35 ) have observed compensatory nephrogenesis (i.e., increased nephron number). Similarly, studies in a novel sheep fetal nephrectomy model also demonstrated compensatory nephrogenesis.…”
Section: Discussionmentioning
confidence: 99%